2008
DOI: 10.1365/s10337-008-0699-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Punicalagin Isomers in Pomegranate Husk

Abstract: Punicalagins are the main ingredients of phenolic compounds in pomegranate (Punica granatum L.) husk. A simple and accurate method for punicalagin analysis based on ethanol extraction and RP-LC using linear gradient of methanol in 0.1% TFA solution was established. The feasibility of this procedure was tested by analyzing the punicalagin level both in fresh pomegranate husk collected from different provinces in China and dried husk from a drugstore. The content of each isomer and total content of punicalagins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 11 publications
7
39
0
Order By: Relevance
“…The results showed that α-punicalagin was more abundant than β-punicalagin. The most abundant compounds among the pomegranate polyphenols are punicalagin isomers [29], which have important antioxidant and atherosclerotic biological properties [30]. The results from the present study showed significant difference among fresh and commercial pomegranate juice, as well as conventional and organic agricultural practices.…”
Section: Antioxidant Capacitymentioning
confidence: 59%
“…The results showed that α-punicalagin was more abundant than β-punicalagin. The most abundant compounds among the pomegranate polyphenols are punicalagin isomers [29], which have important antioxidant and atherosclerotic biological properties [30]. The results from the present study showed significant difference among fresh and commercial pomegranate juice, as well as conventional and organic agricultural practices.…”
Section: Antioxidant Capacitymentioning
confidence: 59%
“…Punicalagin A and punicalagin B interconvert rapidly when in solution to render approximately 30% A and 70% B (Gil, TomasBarberan, Hess-Pierce, Holcroft, & Kader, 2000). These two compounds are named also as a and b anomers of punicalagin (Lu, Ding, & Yuan, 2008;Seeram, Lee, Hardy, & Heber, 2005). In the present study, the proportion of two anomers based on the peak areas were determined approximately as 35% A and 65% B, respectively.…”
Section: Analysis Of the Extracts By Hplcmentioning
confidence: 67%
“…The accuracy of the HPLC method was tested by recovery rates and found as 90.0%, 87.3%, and 95.9% for gallic acid, punicalagin, and ellagic acid, respectively. Punicalagin content of pomegranate peels was reported as between 39.8 and 121.5 mg/g for 16 pomegranate varieties (Lu et al, 2008). Polyphenols of pomegranate peels (only punicalagin A and punicalagin B) were extracted with aqueous ethanol and determined by HPLC in aforementioned study.…”
Section: Analysis Of the Extracts By Hplcmentioning
confidence: 99%
“…The most abundant of the polyphenolic compound in pome-419 granate is punicalagin; punicalagin together with ellagic acid are 420 potent antioxidants, anticancer and have anti-atherosclerotic 421 biological properties (Lu et al, 2008). Furthermore, ellagic acid 422 has shown to be effective as an inhibitor of lipid peroxidation 423 (Hä kkinen et al, 2000;Seeram et al, 2005).…”
mentioning
confidence: 99%